First comes love, then comes marriage, then comes baby in the baby carriage? exploring how women can use leisure as resistance to gendered ideologies. Issue 2 (4th March 2019) - McKeown, Janet K. L.; Parry, Diana C.
ABSTRACT: Although an increasing number of people are identifying as single in western society, gendered ideologies continue to influence women's lives, emphasising the importance of heterosexual couplehood, marriage, family, and biological parenthood. Utilising third wave feminism as our theoretical framework, this paper explores how gendered ideologies can work together to influence adult women's experiences with singlehood. Findings from qualitative interviews with 12 single, adult women, conducted in Ontario, Canada, reveal the ways women can face marginalisation and stigmatisation in certain leisure contexts because of their single status and how the ideology of couplehood can reinforce expectations related to familism and pronatalism for single women. Yet, the findings also illustrate the ways single women can resist these expectations through their leisure. This paper provides an important contribution to the literature, bringing attention to the complex ties between gendered ideologies and leisure for adult women.